PALAEONTOLOGY, AGE, PALAEOENVIRONMENT AND PALAEOECOLOGY OF THE KAREWA INTERMONTANE BASIN OF KASHMIR (J&K, INDIA) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
A rich assemblage of vertebrate fossils, especially fish and mammals, has been recovered from the Plio—Pleistocene Karewa deposits of Kashmir (J & K, India). Microtine rodents and insectivores, including some new taxa and first reports, form the most significant component of the assemblage. The Karewa vertebrate palaeontology is correlated with the magnetic polarity time scale. The Plio—Pleistocene boundary in Karewas is marked by the appearance of microtine rodents. The fossil assemblage is an admixture of high altitude and Iow altitude fauna. The fauna indicates the occurrence of a mosaic of dominant grassland and wooded grassland with some bush cover and wooded areas. A dominant lacustrine with some glacio—fluvial and aeolian environments are indicated for the Karewa sediments.